(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Rural development is primarily concerned with addressing the needs of the rural poor in the matter of sustainable economic activities. The alleviation of rural poverty can be achieved by identifying income-generating activities with a focus on micro finance as the basic input for socio-economic development. There is an existing a huge demand for tiny loans in the country, the progress of the Non-banking financial company (NBFC) microfinance institutions gathered momentum. Microfinance has now been recognized as a potent tool to address the issue of poverty, catering to a niche market earlier occupied by money lenders. Microfinance is unique among development interventions it can deliver these social benefits on an on-going, permanent basis and on a large scale. Microfinance allows poor people to protect, diversify, and increase their sources of income, the essential path out of poverty and hunger. The objective of present study is to examine whether household access to microfinance reduces poverty. Where institutional finance failed Microfinance delivered, but the outreach is too small. There is a question mark on the viability of the Microfinance Institutions. There is a need for an all-round effort to help develop the fledgling Microfinance Industry while tackling the trade-off between outreach and sustainability. This research is based on the primary data collected from field survey carried out by the author in the villages around Pune, it covers Saswad area, Hadapsar area, Baramati area etc. The secondary data used for this study was taken from the PDCC Bank.